COURSE COORDINATION IN VOCATIONAL EDUCATION: A REPORT OF RESEARCH-ACTION DIRECTED FOR MANAGEMENT - Constantino, Paulo [UNESP]; Poletine, Marcia (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
Report a study that aims to uncover and analyze the role of the courses coordinators in vocational education. During the different phases of action research, with interventions by the Supervision of Centro Paula Souza, Sao Paulo, between the years 2011 and 2014, it was realized that the duties set forth in the official guidelines of the institution as well as preponderance of the educational aspects of the administrative decisively driving the roles that these professionals. However, along the way, it is possible that the course coordinator would eventually be associated with the bureaucratic service or the mere service of everyday demands. Overcoming this postulate, we understand that the course coordinator needs to be an active element in the planning and execution of the pedagogical work, an active collaborator in the educational process in the continuing education of their peers and refinement of teaching practices. The results of institutional evaluations demonstrate the contribution that research shares offered in recent years to a focus group of 22 schools.
Keywords: Vocational education; Course coordination; Lifelong education